Solid Goat Milk Soap with Additional Pandan Extract on Chemical Characteristics - Suhendra, Danes; Akmal, Muhamad; Hartati, Lilis; Sutarto, Sutarto; Abdillah, Labib (Bulletin of Applied Animal Research, 2026)
Goat's milk soap has benefits for the skin, like as anti-aging, relieves dry skin conditions, and has compounds that can exfoliate dead skin on the body. In some cases, the use of goat's milk soap can worsen psoriasis or inflammation of the skin, because it uses artificial fragrances and dyes. Fragrances and colorings in soap making can be replaced using natural ingredients such as Secang fennel, butterfly pea flowers, sweet orange peel and pandan leaves. This research aims to analyze the effect of adding pandan leaf extract (Pandanus amaryllifolius) on the chemical quality of solid goat's milk soap, which includes water content, foam stability, free fatty acids and free alkali. The treatments given were without extract (P0), 3.5% extract (P1), and 7% extract (P2). The research used a Completely Randomized Design (CRD) with six replications. The results showed that the addition of pandan extract had a significant effect (P<0.05) on foam stability, where P2 produced the highest stability of 91.99%. However, there were no real differences in water content, free fatty acids and free alkali between treatments. All soap quality parameters, except free alkali, meet Indonesian National Standard 06-3532-2021 standards. Keywords: Goat Milk Soap, Pandan Leaf, Chemical Quality.